2015
DOI: 10.1088/0741-3335/57/11/113001
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary particle-in-cell approach to laser-plasma modelling

Abstract: Particle-in-cell (PIC) methods have a long history in the study of laser-plasma interactions. Early electromagnetic codes used the Yee staggered grid for field variables combined with a leapfrog EM-field update and the Boris algorithm for particle pushing. The general properties of such schemes are well documented. Modern PIC codes tend to add to these high-order shape functions for particles, Poisson preserving field updates, collisions, ionisation, a hybrid scheme for solid density and high-field QED effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
929
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,346 publications
(969 citation statements)
references
References 129 publications
13
929
0
7
Order By: Relevance
“…We verify with PIC simulations using the EPOCH code  (Arber et al 2015) that the instability grows on the observed timescales. We let two initially separated plasma clouds collide.…”
Section: Simulationsmentioning
confidence: 82%
“…We verify with PIC simulations using the EPOCH code  (Arber et al 2015) that the instability grows on the observed timescales. We let two initially separated plasma clouds collide.…”
Section: Simulationsmentioning
confidence: 82%
“…1D simulations have been carried out using the PIC code, EPOCH [28]. We choose a simulation domain spanning [-600, 200] μm in x with 64000 cells.…”
mentioning
confidence: 99%
“…The PIC code EPOCH [15] was used to simulate a defocused laser onto a planar solid target. The spatial size of the simulation box is set to 200 × 120 µm, which is made up of 8000×4800 cells.…”
Section: D Epoch Simulationsmentioning
confidence: 99%